A gradient Sn4+@Sn2+ core@shell structure induced by a strong metal oxide–support interaction for enhanced CO2 electroreduction. Issue 42 (17th October 2022) - Zhang, Shun; Wang, Juan; Wang, Jie; Wang, Kai-Yao; Zhao, Meiting; Zhang, Linlin; Wang, Cheng
Abstract : A gradient Sn 4+ @Sn 2+ core@shell structure induced by a strong tin oxide–g-C3 N4 support interaction enhanced the adsorption and stabilization of CO2 ˙ −, and hence the CO2 RR performances. Abstract : Oxidation states of Sn in tin oxides are hard to regulate due to the uncontrollable evolution during the electrochemical CO2 reduction reaction (CO2 RR), thus limiting the adsorption capabilities and reaction kinetics. Herein, we propose a metal oxide–support interaction-mediated strategy to modify the electronic properties of tin oxides. A gradient Sn 4+ @Sn 2+ core@shell structure was formed as a result of electron transfer from g-C3 N4 to anchored SnO2, unlike reduced graphene oxide (rGO)-supported SnO2 with Sn 4+ -rich surfaces. Such unique structures were revealed by the depth profiles of X-ray photoelectron spectra, and they enhanced the adsorption and stabilization of the *CO2 ˙ − intermediate and accelerated the reaction kinetics. Consequently, SnO2 /g-C3 N4 delivered a faradaic efficiency of 95.1% for the C1 products at −1.06 V, exceeding those of SnO2 /rGO and most reported catalysts. Moreover, the performances were sustained for 70 h without obvious degradation. This work offers an alternative route to efficient catalyst design by combining oxidation state regulation and metal oxide–support interaction and contributes to the development of sustainable technologies for achieving carbon neutrality.